Diphosphahexaarenes as highly fluorescent and stable materials - Hindenberg, Philip; Busch, Marvin; Paul, Alexander; Bernhardt, Moritz; Gemessy, Patrick; Rominger, Frank; Romero-Nieto, Carlos (Angewandte Chemie. International edition, 2018)
Oligoarenes are regarded as subunits of π-extended carbon nanoforms, such as graphene and nanotubes, with exceptional technological importance. Fused arenes can thus provide fundamental insight into the nature of the electronic properties of fused polyaromatic rings and pave the way for the design of extended graphene-like materials. However, large π-extended arenes often show low stability. Herein we report the straightforward preparation of linearly fused diphosphahexaarenes containing two six-membered phosphorus heterocycles. They are highly stable towards air, water, and light over months in both solution and the solid state. Single-crystal X-ray crystallography confirmed the molecular structure of all derivatives. Investigations of their optoelectronic properties revealed that the diphosphahexaarenes exhibit ambipolar redox behavior and high fluorescence quantum yields. Embedding six-membered phosphorus rings into large acenes thus opens up new opportunities for the investigation of polyaromatic systems.